Analisis Tren Penggunaan UGC di Indonesia dan Dampaknya Terhadap Strategi Pemasaran Bisnis - Putri, Liestyaningrum Rahmadhani Wisnu (Journal of Information System, Applied, Management, Accounting and Research, 2025)
This study aims to identify the influence of User-Generated Content (UGC) on business development in Indonesia. Using a systematic review method based on the PRISMA model, 15 articles were selected from Google Scholar and Scopus databases for further analysis. The analyzed articles cover the publication period from 2014 to 2024 and were evaluated for quality using the JBI Critical Appraisal Tools. The findings reveal that UGC plays a crucial role in influencing purchase intention, trust, and brand loyalty. Authentic and relevant UGC is considered more effective than traditional advertising content in building consumer engagement. However, challenges such as fake reviews and content moderation bias must be addressed to maintain UGC credibility. This study also finds that while UGC has significant impacts, company-generated content still plays a vital role in fostering brand loyalty. By leveraging content-sharing motivation and overcoming existing challenges, UGC holds great potential to support digital marketing strategies in Indonesia.